Review of gamified MOOC’s impact toward learner’s motivation in learning effectiveness context - Tan, Wei Kian (2022)
Massive Open Online Courses (MOOC) have become a strong support for building a ubiquitous learning environment typically during Covid19 pandemic. Although more and more Internet users are willing to try MOOC, the problems corresponding to users’ free and autonomous learning are a poor learning experience, low long-term attractiveness to users, and low completion rate of courses. The fundamental reason is that online learning behaviour cannot be well motivated and maintained. A key design concept related to the MOOC is gamification design - the application of game design elements to non-gamification scenarios. Some MOOC has integrated different gamification method to attract users. However, the academic community’s attitude towards gamification still inconsistent, and even some studies believe that the level of user motivation in the gamified design condition will decrease. From the perspective of user information behaviour, this paper follows the logical route of “motivation-behaviour” and analyse the perceptual challenge and perceptual attention, learning results and cognitive user participation. From the MOOC context, this paper discusses the technical application factors that affect user behaviour and enriches the research direction in the field of information behaviour. Lastly, this study puts forward some development suggestions to MOOC operators to comprehensively improve the perception challenge and attention of MOOC users and enhance their learning effect.